1977
DOI: 10.1017/s0014479700007808
|View full text |Cite
|
Sign up to set email alerts
|

Diallel Analysis of Genetic Variation in Pigeon Pea (Cajanus cajan)

Abstract: SUMMARYA diallel analysis of flowering time, pod number, 100-seed weight and yield of six cultivars of Cajanus cajan (L.) Millsp. was studied. Additive inheritance was important in determining flowering time, but the dominance component was higher than the additive component, and over-dominance was observed for pod number, 100-seed weight and yield. Heritability estimates for all the traits except flowering time were quite low, and the bulk population method of breeding was suggested for early segregating gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Predominance of additive genetic effects on the inheritance of HSW was also reported in previous studies using grain pigeonpea (Sharma et al 1973;Dahiya and Brar 1977;Abrams et al 1978;Awatade et al 1980;Venkateswarlu and Singh 1982;Sinha et al 1987;Mehetre et al 1988). In contrast, others (Reddy et al 1979;Mohamed et al 1985;Mehra et al 1986;Sardana et al 1987;Gartan et al 1989) found non-additive effects to be more important than additive effects, while Malik et al (1985) and Ghodke et al (1993) found additive and non-additive effects to be equally important in the inheritance of HSW.…”
Section: Discussionsupporting
confidence: 68%
“…Predominance of additive genetic effects on the inheritance of HSW was also reported in previous studies using grain pigeonpea (Sharma et al 1973;Dahiya and Brar 1977;Abrams et al 1978;Awatade et al 1980;Venkateswarlu and Singh 1982;Sinha et al 1987;Mehetre et al 1988). In contrast, others (Reddy et al 1979;Mohamed et al 1985;Mehra et al 1986;Sardana et al 1987;Gartan et al 1989) found non-additive effects to be more important than additive effects, while Malik et al (1985) and Ghodke et al (1993) found additive and non-additive effects to be equally important in the inheritance of HSW.…”
Section: Discussionsupporting
confidence: 68%
“…Based on classification by Saxena and Sharma (1990), low heritabilities were observed in grain yield (0.28) and seeds per pod (0.4), medium heritabilities in days to maturity (0.67), number of primary branches (0.58) and 100 seed mass (0.63), and high heritabilities in days to flowering (0.75) and plant heights (0.82). Dahiya and Brar (1977) also reported similar varying heritabilities in these traits in pigeonpea. Because traits with high heritabilities are the most reliable as germplasm descriptors (Abu-Alrub et al 2004), plant height, days to flower, days to maturity and 100 seed mass could be used for pigeonpea germplasm classification.…”
Section: Broad-sense Heritabilitymentioning
confidence: 57%
“…Hence, the pedigree breeding efforts will not be effective in the genetic enhancement of seed protein in pigeonpea. Reddy et al (1979), Reddy and Singh (1981), and Durga (1989) reported the presence of dominance or partial dominance of low protein and confirmed the views of Dahiya and Brar (1977) on breeding strategy. Recently, Saxena and Srivastava (2023) selected a transgressive segregant for high seed protein in pigeonpea, and they attributed it to the complementation of diverse high‐protein alleles present in the two parents.…”
Section: Introductionmentioning
confidence: 66%
“…In pigeonpea, the first such study was conducted by Dahiya et al (1977) involving pigeonpea genotypes and reported significant maternal effects for seed proteins. While studying the inheritance of this trait, Dahiya and Brar (1977) speculated that there were three to four protein‐controlling genes in pigeonpea. They also concluded that since the additive genetic variances for protein content were nonsignificant, it will lead to low heritability and poor genetic advance.…”
Section: Introductionmentioning
confidence: 99%